A new γ-spectroscopy station at the University of Athens - Lagaki, V.; Kouvaris, E.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
A new γ-spectroscopy station at the University of Athens has been recently deployed. The station is built around a 25% HPGe detector and aims at supporting the environmental radioactivity studies program of the NuSTRAP group at UoA. The detector needs detailed characterization of its efficiency and calibration over a rather wide range of energies. Besides standard calibration point sources (60Co, 137Cs, 152Eu and 226Ra), detector simulations using the Monte Carlo N-particle transport code (MCNP) were performed. Results of the MCNP calculations are shown and compared with real spectra showing satisfactory agreement